Pengetahuan, sikap tentang ASI (Air Susu Ibu) dan keterampilan suami ibu nifas dalam melakukan metode SPEOS (Stimulasi Pijat Endorphin, Oksitosin, dan Sugestif) - Nanda Wilda Lestari; Susmiati Susmiati; Lili Fajria (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Knowledge, attitudes about breast milk and skills of the husbands of postpartum mothers in the SPEOS method Background: Breastfeeding is a natural process for a mother to support and prosper her child after childbirth. The husband's role by providing support to breastfeeding mothers affects the success of breastfeeding.Purpose: To know the knowledge, attitudes about breast milk and the skills of the postpartum husband in performing the SPEOS method (Endorphin, Oxytocin and Suggestive Massage Stimulation)Method: Quantitative research with the research design